State, society, and land in Jordan - Fischbach, Michael R. (Social, economic, and political studies of the Middle East and Asia, 2000)
Examines how state and society conceptualized land ownership in Jordan from the late Ottoman era through the 1950s, and how the resulting interaction between them shaped the socio-economic and political contours of modern Jordan.